Croton lechleri lyophilized extract gel effect on Oryctolagus cuniculus` pulp tissue - Correa-Olaya, Eufemia Isabel (2021)
Objective. To determine the effect of the Croton lechleri lyophilized extract gel on root pulp tissue of pulpotomies performed on Oryctolagus cuniculus. Methods. Thirty-two two-month-old male New Zealand rabbits race, were randomly assigned into four experimental groups: a) control, b) formocresol, c) 1% Croton lechleri and d) 2.5% Croton lechleri. Four pulpotomies were done on each animal. Clinical variables (abscesses, tooth mobility and infections) and histopathological variables (fiber formation, pro-inflammatory cell and regenerative cell number) were analyzed after 1,7,15, and 30 days. Results. No clinical signs were evident in all experimental groups evaluation at any time period. In the first day histopathological evaluation, there were abundant presence of capillaries in all control group samples and half of formocresol ones, while 1% Croton lechleri and 2.5% Croton lechleri groups, had a moderate number in all samples. In the 7,15 and 30 evaluation days, the number of capillaries was higher in formocresol group than the others. The 2.5% Croton lechleri group, showed a lower number of inflammatory cells (macrophages and lymphocytes), a higher number of repair cells (fibroblasts, odontoblasts) and normal collagen fibers than the others, over all evaluated times. Conclusions. The 2.5% Croton lechleri lyophilized extract gel showed a greater anti-inflammatory, healing and regenerating effect on the pulp tissue compared to the other experimental groups.